High frequency measurement of dielectric properties for packaging materials - Lim, Ying Ying (2008)
This thesis summarizes the purpose and milestones covered in the process of carrying out the project. Essentially, the project proposes to develop and implement a suitable method to measure the complex permittivity of thin (l-3mm) packaging materials used in the microelectronics industry. Apart from being able to measure over a large bandwidth from 0.1 -20 GHz and be relatively low cost and easy to implement, the technique also has to be reasonably accurate as compared to other available methods.